1972
DOI: 10.1113/expphysiol.1972.sp002164
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Mast Cells in Vasodilatation Due to Axon Reflexes in Injured Skin

Abstract: Immediately subjacent to a scratch damaging the epidermis of the external ear of the albino rat, all the dermal mast cells are degranulated. The Although mast cells occur in peripheral nerves [Olsson, 1968] and, in some mammals, in the central nervous system [Campbell and Kiernan, 1966; Kruger, 1970], no report has been found in the literature indicating whether these cells are subject to any form of nervous control. Electron microscopic studies in the central nervous system [Flood and Kruger, 1970 Wiedma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…The airway mast cell must be considered as a candidate since mast cells are known to synthesize peptidoleukotrienes, and substance P has been found to stimulate certain types of mast cells as monitored by histamine release (Fewtrell et al 1982;Devillier et al 1985). Furthermore, mast cells have long been implicated in contributing to capsaicin-sensitive neuronal responses in the skin (Kiernan, 1971(Kiernan, , 1972(Kiernan, , 1975. However, neither EFS, capsaicin, or substance P evokes measurable quantities of histamine release from the guinea-pig trachea or bronchus (Undem, Adams & Buckner, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The airway mast cell must be considered as a candidate since mast cells are known to synthesize peptidoleukotrienes, and substance P has been found to stimulate certain types of mast cells as monitored by histamine release (Fewtrell et al 1982;Devillier et al 1985). Furthermore, mast cells have long been implicated in contributing to capsaicin-sensitive neuronal responses in the skin (Kiernan, 1971(Kiernan, , 1972(Kiernan, , 1975. However, neither EFS, capsaicin, or substance P evokes measurable quantities of histamine release from the guinea-pig trachea or bronchus (Undem, Adams & Buckner, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A neurogenic component of the inflammatory response has been previously demonstrated for capsaicin (Jancso et al, 1967) and formalin (Brown, Kissel & Lish, 1968 humour' is liberated on stimulation of sensory nerves. Kiernan (1972a) Kiernan, 1972b;prostaglandin E1-Crunkhorn & Willis, 1971 (Moncada, Ferreira & Vane, 1973;Williams & Morley, 1973) and it is possible that the combination of bradykinin and prostaglandin E, produced so much more stimulation of the sensory nerves than either bradykinin or prostaglandin E1 alone, and also enhancement of the effects of the amines released from the partially depleted mast cells, that the effect of compound 48/80 was masked. It is concluded that those irritants which produce neurogenic oedema cause release of one or more substances from sensory nerve terminals, and that at least part of the oedema produced is mediated by amines released from mast cells ( Figure 5).…”
Section: Capsaicin Pretreatmentmentioning
confidence: 99%
“…The object of the experiments on capsaicin-desensitized rats reported here was a more quantitative examination of the extent to which sensory nerve stimulation contributes to the oedema produced by a variety of irritants. Since Kiernan (1972a) has suggested that mast cells are involved in antidromic vasodilatation, another series of experiments was performed in which rats were pretreated with compound 48/80, to establish the role of mast cells as mediators of neurogenic oedema.…”
Section: Introductionmentioning
confidence: 99%
“…The stress-induced increased expression of substance P (SP) in skin nerve fibers and of cutaneous nerve growth factor (NGF) consequently lead to the development of neurogenic skin inflammation, recognized by its classical features of mast cell degranulation, vasodilatation, and plasma extravasation [12,13]. Both SP and NGF are now widely acknowledged as cardinal immunomodulators and prevailing stress markers in different settings [4,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%